SensoryX ’21 Workshop on Multisensory Experiences at ACM IMX ’21 - Covaci, Alexandra; Saleme, Estêvão Bissoli; Ghinea, Gheorghita (Proceedings of the Workshop on Multisensory Experiences (SensoryX); 2021: Proceedings of the 1st Workshop on Multisensory Experiences - SensoryX'21DO - 10.5753/sensoryx.2021.15682, 2021)
Multisensory experiences have been increasingly undertaken in the digital world. With the emerging interest in immersive applications (i.e. 360 videos and virtual reality), more and more researchers and practitioners are in pursuit of ways to take these experiences to the next level, adding sensations that go beyond that of seeing and hearing. This one-day workshop aims at identifying the current practices, challenges, opportunities, and limitations to be overcome in the quest to transcend the overwhelmingly bisensorial nature of digital multimedia into a multisensory one by fostering discussions on the use of olfactory, gustatory and tactile eﬀects in digital experiences.